Based on network pharmacology and molecular docking to study the mechanisms of active ingredients of ginseng in the treatment of atopic dermatitis - BU Jialiang; SHEN Lin; MENG Yuan; PIAO Yingshi (Pifu-xingbing zhenliaoxue zazhi)
[Objective] Using network pharmacology and molecular docking techniques to analyze the molecular mechanisms of active ingredients of ginseng in the treatment of atopic dermatitis. [Methods] The databases of OMIM, TTD, CTD, GEO and GeneCards were used to screen the homologous targets and disease targets of active ingredients in ginseng. Then the ″drug-component-target″ network was constructed, and the potential and core targets of ginseng for the treatment of atopic dermatitis were screened. GO functional enrichment and KEGG pathway analysis were performed on the overlapping targets of active ingredients in ginseng and AD. Finally, the binding ability of active ingredients to TOP4 core targets was verified through molecular docking, and the docking results were visualised. [Results] A total of 22 active ingredients and 106 targets were identified. The GO functional enrichment showed that the biological processes were mainly involved in inflammatory response and regulation of secretion, etc., while the molecular function was mainly involved in the binding of nuclear receptor and cytokine receptors, etc. Among the cellular components, receptor complex and membrane rafts accounted for a large proportion. KEGG enrichment analysis identified 156 signaling pathways, including IL-17, TNF and other signaling pathways. Molecular docking results showed that all of the active compounds of ginseng had low binding energy to the TOP4 core targets, among which arachidonate, panaxadiol and stigmasterol had very high affinity to the core target IL-1β. [Conclusions] Ginseng has the potential to treat atopic dermatitis. Arachidonate, panaxadiol and stigmasterol may be the key monomeric components of ginseng for the treatment of AD, and they probably play a therapeutic role through interacting with IL-1β.